PENGARUH PENERAPAN MODEL JIGSAW TERHADAP HASIL BELAJAR TEMATIK KELAS IV SEKOLAH DASAR - Rizky Herman Susilo; Suhardi Marli; Asmayani Salimi (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to analyze the effect of the application of the Jigsaw model on student learning outcomes in Thematic learning grade IV 54 Pontianak Elementary School. The research method used was an experimental, non-equivalent group design type Quasi Experimental from. The study population was all students of class IV 54 Pontianak Elmentary School in West Pontianak, totaling 62 students. The sampling technique uses purposive sampling. The research technique used is the measurement technique. Data collection tool in the from of multiple choice tests. The results of the data analysis namely, the acerage score of the control class post-test was 62,968 and the experiment was 67,097. Based on the results of the t-test calculations obtained tcount 2.004 > t table 2,000 then Ha is accepted. This shows that there is an influece of student learning outcomes by applying the Jigsaw model. Calculation of effect size of 0,51 with moderate criteria. The conclusion of this study is that there is an effect of the application of the Jigsaw model to student learning outcomes in Thematic learning grade IV of 54 Pontianak Elementary School in West Pontianak in the medium category. Keywords : Jigsaw Model, Learning Outcomes, Thematic.